Evaluation of in vivo immunotoxicity for Ho3+-doped Gd2O3 nanoparticles as dual-modality nanoprobes. (June 2020) - Tian, Xiumei; Liu, Ziying; Zeng, Ao; Wang, Haiyan; Lou, Jiamin; Wei, Yuezi; Man, Yuhong; Li, Li; Yang, Fanwen
Graphical abstract: As dual-modality nanoprobes, the nano-structure of HoNPsmay reduce in vivo immunotoxicity. Therefore, it will be crucial to evaluate the expression levels of CD25, CD69, and CD71 in peripheral blood, as well as the expression levels of P38, ERK, JNK, and P53 in the liver, at 7 d after injection of these rare-earth-based biomaterials before molecular imaging in vivo . Abstract: Rare-earth-doped gadolinium-oxide (Gd2 O3 ) nanoparticles (NPs) are increasingly used for magnetic resonance imaging (MRI) and optical imaging (OI). However, to date, the poor data of in vivo hazard assessment has been one obstacle to its clinical deployment, especially the relative immunotoxicity in vivo . In this paper, we synthesized Ho 3+ -doped Gd2 O3 NPs (HoNPs) for MRI and OI by laser ablation in liquid. To the best of our knowledge, we present here the most extensive biocompatibility in vitro (cell viability and apoptosis) and in vivo relative immunotoxicity (the level of cluster-of-differentiation (CD) markers in peripheral blood and relative gene expression of toxicity in the liver) in Balb/c mice. Our results indicate that HoNPs with satisfactory biocompatibility can be used as MRI (r1 relaxivity of 5.01 mM-1 s-1) and OI (strong blue fluorescence) dual-modal contrast agents in vitro . Importantly, there were significant differences in the expression levels of CD25, CD69, CD71, protein 38 (P38), extracellular regulated protein kinase (ERK), c-Jun N-terminal kinase (JNK), and protein 53 (P53) between the negative control and the HoNPs at 7 d after injection (p < 0.05). In conclusion, this work suggests that the nano-structure of HoNPs may reduce in vivo relative immunotoxicity. Therefore, it will be crucial to evaluate the above- mentioned indexes on in vivo relative immunotoxicity at 7 d after injection of these rare-earth-based biomaterials before molecular imaging in vivo .